역함수를 이용한 치환적분
http://bomber0.myid.net/ (토론)님의 2009년 8월 22일 (토) 20:02 판
\(\int f(x)\,dx=xf(x)-\int xf'(x)\,dx+xf(x)-\int f^{-1}(f(x))f'(x)\,dx+xf(x)-G(f(x))\)
여기서 \(G(x)= \int f^{-1}(x)\,dx\)
문제
\(\int \sqrt{\frac{x}{1-x}}\,dx\)
\(G(x)=\int f^{-1}(x)\,dx= \int\frac{x^2}{1+x^2}\,dx=\int(1-\frac{1}{1+x^2})\,dx=x-\arctan x+C\)
따라서,
\(\sqrt{\frac{x}{1-x}}\,dx=(x-1)\sqrt{\frac{x}{1-x}}+\arctan{\sqrt{\frac{x}{1-x}}}+C\)
\(\int \sqrt{\frac{x}{1-x}}\,dx= (x-1)\sqrt{\frac{x}{1-x}}+\arctan{\sqrt{\frac{x}{1-x}}}+C\)